Te hare tu propio librero = I'll build you a bookcase - Fahey, Jean Ciborowski, 1949-; Shin, Simone; Canetti, Yanitzia, 1967-; Fahey, Jean Ciborowski, 1949-; Fahey, Jean Ciborowski, 1949- (New York : Lee & Low Books, Inc., 2021)
Illustrations and rhyming text portray a loved one who promises to build a home library to hold treasures that grow and change along with their special child.
Ages 4-6.
Grades K-1.
Parallel text in English and Spanish.
Keywords: Stories in rhyme; Bookcases -- Fiction; Books and reading -- Fiction; Spanish language materials -- Bilingual; Stories in rhyme; Bookcases -- Juvenile fiction; Books and reading -- Juvenile fiction; Picture books